Multiple osteocartilaginous exostoses of the lower extremity: A case report. Issue 1 (March 2015) - Shtofmakher, Garry; Kaufman, Michelle A.; Bhoola, Prashant H.; Patel, Ankur A.; Rice, Susan M.; Cohen, Randy E.
Highlights There is potential for malignant transformation into chondrosarcoma in individuals with MHE, and thus lifelong monitoring will be necessary. If an osteochrondroma becomes larger, or increasingly painful surgical intervention should be considered for these patients. Multiple osteochondromatois is often an incidental finding and is usually not on the list of differential diagnoses. MHE is inherited in an autosomal dominant pattern through a defect in the EXT gene loci. An osteochrondroma at the 1st MTPJ contributed to increased bunion pain due to mechanical irritation of the shoegear against the exostosis.